A revised top-down theory of the mind: Commentary on Otto Kernberg's "Some Implications of New Developments in Neurobiology for Psychoanalytic Object Relations Theory". Issue 1 (2nd January 2022) - Fisher, Charles P.
ABSTRACT: This commentary on Otto Kernberg's paper, "Some Implications of New Developments in Neurobiology for Psychoanalytic Object Relations Theory, " proposes that psychoanalytic object relations theory has implications for research in neurobiology, in addition to the implications of new developments in neurobiology for psychoanalysis, which are addressed by Kernberg. The commentary considers Kernberg's recommendations for revisions in psychoanalytic drive theory and the theory of the dynamic unconscious, in relation to identifying and enumerating the drives themselves and the development of the dynamic unconscious. The commentary also addresses the topics of conflict, the death drive, therapeutic implications, and neurobiological concepts of object representations in the brain and mind. There are apparent tensions between Otto Kernberg's view of self-object-affect relations as "building blocks of the mind" and Mark Solms' view that "all our relationships with the external object world are, at bottom, driven by our libidinal needs." This commentary explores that apparent tension and finds that it frames a generative dialogue between psychoanalysis and neuroscience. The commentary ends with a suggestion for neuropsychoanalytic research connecting object representations with brain mechanisms. Previous work by Otto Kernberg on the topic of mourning is juxtaposed with neuroscience research by Mark Solms, Peter Freed, and their respective colleagues.